Diversion Under Malaysian Juvenile Justice System: a Case of Too Little Too Late? - Aminuddin, Mustaffa (Springer Netherlands, 2016)
The concept and practice of diversion are not a novel phenomenon. For many years, diversion from formal adjudication by court has been widely adopted as an important feature of various juvenile justice systems across the countries. There are different forms of diversion programmes which have been designed and implemented with the aim to divert children from direct contact with formal criminal process. Various researches on diversion programmes have disclosed positive impacts on their effectiveness in handling children in conflict with the law. This article focuses on criminal process under current Malaysian juvenile justice, in which the concept of diversion is still a strange subject. It highlights issues under current juvenile criminal justice and examines the possibility of integrating diversion programmes as alternative measures to deal with children in conflict with the law. Introduction of diversion programmes as part of the current system is seemed as potential alternative measures to improve the effectiveness of the current Malaysian juvenile justice system.